Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.adaj.2015.09.012
|View full text |Cite|
|
Sign up to set email alerts
|

Dental disease patterns in methamphetamine users

Abstract: Background The authors used a large community sample of methamphetamine users to verify the patterns and severity of dental disease and establish a hierarchy of caries susceptibility by tooth type and tooth surface. Methods Using a stratified sampling approach, 571 MA users received comprehensive oral examinations and psychosocial assessments. Three calibrated dentists characterized the dental and periodontal disease using National Health and Nutrition Examination Survey (NHANES) protocols. Data were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
1
36
0
5
Order By: Relevance
“…According to a systematic review of MA use and health outcomes among adolescents, there is insufficient evidence of an association between dental outcomes and MA use [33]. Nonetheless, another study showed higher rates of dental disease among adult people who use MA [34]. In fact, dental disease as one of the most important comorbidities in PWUD is a reasons to develop treatment plans that address both oral health problems and drug use [34].…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review of MA use and health outcomes among adolescents, there is insufficient evidence of an association between dental outcomes and MA use [33]. Nonetheless, another study showed higher rates of dental disease among adult people who use MA [34]. In fact, dental disease as one of the most important comorbidities in PWUD is a reasons to develop treatment plans that address both oral health problems and drug use [34].…”
Section: Introductionmentioning
confidence: 99%
“…Although Slade et al stated that edentulism will be limited geographically, the economy, the lack of benefits associated with many jobs, the use of methamphetamine and the soft drink, Mountain Dew, have resulted in many younger people in Iowa getting teeth extracted. These persons will continue to be edentulous as they age.…”
Section: Discussionmentioning
confidence: 99%
“…In a large urban sample of 571 methamphetamine users, Shetty et al found that 40 percent of participants felt embarrassed about their dental appearance. 45 Promoting dental health and addressing aesthetic concerns can be a powerful tool to increase mood, confidence, and attitudes towards change. Collaboratively create a treatment plan that focuses on attainable goals centered on harm reduction.…”
Section: Empathetic Communication Throughout Treatment Enhances Outcomesmentioning
confidence: 99%
“…"Whereas 37% of adults aged 35 to 49 years in the US general population have total periodontitis, more than 89% of the MA users showed total periodontitis". 45 Xerostomia and dehydration associated with meth use (mediated by alpha-2 receptors in the brain) causes users to crave FACTORS INFLUENCING THE USE OF METHAMPHETAMINE BY DENTAL PATIENTS IN THE UNITED STATES [290][291][292][293][294][295][296][297] sugar, and these individuals crave and typically drink "large quantities of soft drinks". 43 Additionally, oral hygiene may suffer significantly during periods of heavy drug use.…”
Section: Empathetic Communication Throughout Treatment Enhances Outcomesmentioning
confidence: 99%